ФОРМУВАННЯ ЕКОЛОГІЧНОЇ СВІДОМОСТІ МАЙБУТНІХ УЧИТЕЛІВ БІОЛОГІЇ: УЗАГАЛЬНЕННЯ РЕЗУЛЬТАТІВ ДОСЛІДЖЕННЯ (Педагогіка вищої та середньої школи, 2008)
The results of the experimental research concerning the problem of environmental consciousness forming have been generalized in the article; the dynamics of levels in environmental consciousness forming has been canalized in the process of Biology teachers’ training.